Development of e-pub-based e-modules on plant structure and development to improve students' problem-solving skills - Ardian, M. Ferli; Sari , Murni Sapta; Setiowati , Frida Kunti (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
One of the efforts to train and improve problem-solving skills is by developing teaching materials in the form of e-pub-based e-modules that contain problem-based learning. This research aims to produce e-modules based on e-pub plant structure and development that are valid, practical, and effective. The development of teaching materials follows the ADDIE instructional design model. The instruments used were e-pub-based e-module validation sheets by expert lecturers as well as student response questionnaires and pretest-posttest scores of problem-solving skills analyzed using the One Way Ancova test. The results of research and development showed that the acquisition of validation scores by teaching material experts was 100%, material experts were 100%, education practitioners were 99%, student response results were 87.05% and effectiveness results were 0.009<0.05 so the use of e-pub-based e-modules was effective in the learning process. The conclusion of the study is that the epub-based e-module is very valid, very practical, and effective as a teaching material that can be used by students in learning.